Wireless cycling posture monitoring based on smartphones and bluetooth low energy - Maio, António F. (2015)
This work presents the implementation of a wireless network based on Bluetooth Low Energy (BLE) which enables the integration of multiple sensor nodes into a smartphone-based system in order to monitor the posture of cyclists. The developed posture monitoring system obtains the orientation in space of each body segment in which the sensor nodes are placed and calculates the trunk angle, the knee angle and the angle of inclination of the road. Raw sensor data are collected periodically from accelerometers, magnetometers and gyroscopes and sent via BLE to an Android smartphone, which plays the role of central station and performs the data processing concerning the posture calculation. We describe the development of the hardware and software of the sensor nodes, which are based on the CC2540 BLE system-on-chip, as well as the development of the Android application, and provide experimental results concerning the measurement of the posture of a cyclist in order to validate the proposed system.